(3CQHYhf MOjkKG aj GdWHs
(3ChdgG (B:s
(3GdMeO ddg GdTGai ef GdCeQGV hGdYdd aEf GdadGSaI GdbOeGA McehG HGH GdcGed GdaVd hGdehUha HfgGjI GdYbd s
(3BNQgG (B:s
(3Yf CHj gQjQI QVi Gddg Yfg bGd (B: (3gGLQ GdfHi Udi Gddg Ydjg hSde agGLQJ Ke LdSJ aGdJaJ Edi QShd Gddg Udi Gddg Ydjg hSde abGd (B: (3Cjchf ? bdJ (B: (3fYe , bGd be aUd , aEf GdUdGI TaGA (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs